THE EVOLUTION OF FINANCIAL TERMS IN MODERN ENGLISH (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article examines the diachronic evolution of financial terminology in Modern English, tracing its development from the late medieval period to the digital age. The research employs a mixed-methods approach combining corpus linguistics analysis of historical texts with etymological investigation to identify patterns of lexical innovation, borrowing, and semantic shift. Key findings reveal three distinct evolutionary phases: the Early Modern period characterized by Romance borrowing (15th-17th centuries), the Industrial Revolution era marked by Germanic compounding (18th-19th centuries), and the Contemporary Digital period featuring extensive neologism creation (20th-21st centuries). The study demonstrates how financial terminology has evolved from concrete, tangible concepts (e.g., 'tally stick') to increasingly abstract and metaphorical constructs (e.g., 'cryptocurrency', 'blockchain'), reflecting broader socioeconomic transformations. This linguistic evolution mirrors the financialization of global economies and the digital revolution's impact on economic discourse.
Keywords: Financial terminology, lexical evolution, economic discourse, borrowings in English, neologisms, globalization, semantic shift, digital finance, banking vocabulary, linguistic innovation.